Lolita’s Love Affair with the English Language: Heterolingualism and Voice in Translation - Vale de Gato, Margarida (Meta, 2018)
This article is a first-person account of the translation of Lolita into Portuguese dealing primarily with the question of how to treat English as a source language that should be replaced by the translating language. The novel foregrounds the narrator’s stridency as a non-“native illusionist” (Nabokov 1955/1991: 317), along with a heterolingual bend, presenting remarkable challenges for translation: how to represent the geopolitics of linguistic hybridity in the TT and how to maintain the ambiguity of alignments between (implied) reader(s), author(s) and competing instances of narratorial authority, including the “fictional translator” (Klinger 2015: 16).Selective non-translation is suggested as an option for addressing linguistic hybridity through which, in this context, the “differential voice(s)” (Hermans 2007; Suchet: 2013) might foreground linguistic (and hence cultural/ideological) difference and deviation. The adherence to a strategy of “overt translation” (House 2001) is not intended to break the “translator’s pact” (Alvstad: 2014); it refuses, however, the convention of transparency as one of its tenets. It also shifts the focus from phonocentric authority to a polyphonous palimpsest and an archaeology of language(s) – not an entrenched foreignization, but an availability for “other-languagedness” (Bakhtin: 1981).